TRADISI TAHLILAN DAN YASINAN - Rhoni Rodin (IBDA` : Jurnal Kajian Islam dan Budaya, 2013)
This paper discusses about the values which contain in tahlian andyasinan in Muslim societies as aseries activities in takziyah. Takziyah isvisiting the family which one of the member is died.this research is intendedto know the detail activity of tahlian and yasinan which becomethe source to dig up the values inside. Both tahlian and yasinan containsspecial values which support the live of the society and it mixes with thelocal culture.